Inhibitory effect of mammea E/BB from Mammea siamensis seed extract on Wilms' tumour 1 protein expression in a K562 leukaemic cell line - Rungrojsakul,M. (Taylor and Francis Ltd., 2015)
© 2015 Taylor & Francis Mammea siamensis is used in traditional Thai medicine. This study was designed to extract and isolate an active compound from the M. siamensis seeds and to investigate its activity on Wilms' tumour 1 (WT1) protein expression in K562 cells. WT1 is a transcription factor that stimulates cell proliferation. The ethanol saraphi seed (ESS) extract was fractionated using n-hexane, ethyl acetate, n-butanol and water to obtain n-hexane saraphi seed (HSS), ethyl acetate saraphi seed (EASS), n-butanol saraphi seed (BSS), and water saraphi seed (WSS) extracts, respectively. The ESS, HSS and EASS extracts had strong cytotoxic effects on K562 cells in the MTT assay. All three fractions decreased WT1 protein levels and decreased total cell numbers. The HSS extract decreased the WT1 protein levels in a time- and dose-dependent manner. HPLC and NMR analyses indicated that the active compound of HSS was mammea E/BB. M. siamensis seeds are thus identified as a promising source of bioactive compounds for potential inhibition of WT1 protein expression.